Impact of maternal diabetes on neonate: Maternal Diabets effect on neonate (Journal of the Medical College for Women & Hospital, 2026)
Background: Maternal diabetes, including gestational diabetes mellitus (GDM) and pregestational diabetes, is a major determinant of neonatal complications. Aim:This study aimed to evaluate the immediate complications in infants of diabetic mothers (IDM).Materials and Method: A hospital-based observational study was conducted at the Department of Pediatrics, Medical College for Women and Hospital, from July 2024 to July 2025. A total of 120 neonates born to mothers with GDM or pregestational diabetes were included. Data on maternal diabetes type, glycemic control, mode of delivery, neonatal birth weight, clinical presentation, and complications—such as hypoglycemia, hyperbilirubinemia, hypocalcemia, respiratory distress, and polycythemia—were collected. Statistical analysis was performed using SPSS 26.Results: Of the 120 neonates, 54.17% were male. Most mothers had GDM (70.83%) and good glycemic control (HbA1c